Linalool Odor-Induced Anxiolytic Effects in Mice - Harada, Hiroki; Kashiwadani, Hideki; Kanmura, Yuichi; Kuwaki, Tomoyuki (Frontiers in Behavioral Neuroscience, 2018)
In folk medicine, it has long been believed that odorous compounds derived from plant extracts can have anxiolytic effects. Among them, linalool, one of the terpene alcohols in lavender extracts, has been reported to have the anxiolytic effects. However, the anxiolytic nature of the linalool odor itself as well as its potential action through the olfactory system has not been thoroughly examined. In this study, we examined the anxiolytic effects of linalool odor with light/dark box test and with elevated plus maze, and found that linalool odor has an anxiolytic effect without motor impairment in mice. The effect was not observed in anosmic mice, indicating that it was triggered by olfactory input evoked by linalool odor. Furthermore, the effect was antagonized by flumazenil, indicating that the linalool odor-induced anxiolytic effect was mediated by GABAergic transmission via benzodiazepine-responsive GABAA receptors. These results provide information about the potential central neuronal mechanisms underlying the odor-induced anxiolytic effects and the foundation for exploring clinical application of linalool odor in anxiety treatments.